Dipeptidyl peptidase-4 inhibitor reduces infarct size and preserves cardiac function via mitochondrial protection in ischaemia-reperfusion rat heart - Chinda K. (2014)
Aim: We hypothesized that dipeptidyl peptidase (DPP)-4 inhibitor (vildagliptin) reduces fatal arrhythmias, cardiac dysfunction and infarct size caused by ischaemiareperfusion (I/R) injury via its attenuation of cardiac mitochondrial dysfunction. Methods: In total, 26 rats were randomized to receive either 1 mL normal saline solution or 2.0 mg/kg vildagliptin intravenously (n = 13/group) 30 min prior to a 30-min left anterior descending coronary artery occlusion, followed by a 120-min reperfusion. Arrhythmia scores, cardiac functions, infarct size and mitochondrial function were evaluated. Results: Vildagliptin reduced the infarct size by 44% and mitigated cardiac dysfunction by preserving cardiac function without altering the incidence of cardiac arrhythmias. Vildagliptin increased expression of Bcl-2 and pro-caspase3 in the ischaemic area, whereas Bax and phosphorylated-connexin43/total-connexin43 were not altered. Vildagliptin attenuated cardiac mitochondrial dysfunction by reducing the reactive oxygen species level and mitochondrial swelling. Conclusions: DPP-4 inhibitor provides cardioprotection by reducing the infarct size and ameliorating cardiac dysfunction in I/R hearts by attenuating cardiac mitochondrial dysfunction and cardiomyocyte apoptosis. © 2013 The Author(s).